Metabolite profiling of chickpea (Cicer arietinum) in response to necrotrophic fungus Ascochyta rabiei - Raman, Rosy; Morris, Stephen; Sharma, Niharika; Hobson, Kristy; Moore, Kevin (Frontiers in Plant Science, 2024)
Ascochyta blight (AB) of chickpea caused by the necrotrophic fungus Ascochyta rabiei is one of the most significant diseases that limit its the production of chickpea. Here, we present metabolite profiling of two chickpea accessions comprising a moderately-resistant breeding line (CICA1841) and a highly susceptible cultivar (Kyabra) in response to A. rabiei infection. Non-targeted metabolomics analysis using liquid chromatography-mass spectrometry (LC-MS) revealed constitutive or differentially altered metabolites in aerial tissue (leaf and stem) of CICA1841 and Kyabra in response to infection. We have identified putative metabolites associated with resistance and susceptibility to one of the highly aggressive Australian A. rabiei isolates TR9571. The mass abundance of Ferulic ferulic acid was high in the moderately resistant accession breeding line compared to the susceptible cultivar. So, a low level of ferulic acid in Kyabra could, therefore, contribute to susceptibility to A. rabiei. In contrast, the levels of Catechinscatechins, Phthalic phthalic acid, and Nicotinic nicotinic acid were high in the aerial tissue of the susceptible cultivar. Furthermore, Salicylic acid (SA) was induced in the tissue of the susceptible cultivar after fungus colonization, while D-Xylose and Methyl Jasmonate (MeJA) were reduced. The host-pathogen interaction resulted in the accumulation and suppression of various metabolites, revealing a possible reason for susceptibility against A. rabiei in the highly susceptible chickpea cultivar. Interestingly, the mass abundance of salicylic acid was induced in the aerial tissue of the susceptible cultivar after fungus colonization, while methyl jasmonate (MeJA) was reduced, elucidating the key role of phytohormones in chickpea-A. rabiei interaction. Several differential metabolites are the precursors forrepresenting secondary metabolic pathways, including flavonoid biosynthesis, phenylalanine pathway, Aminoacyl-tRNA biosynthesis, pentose and glucuronate interconversions, arginine biosynthesis, valine, leucine, and isoleucine biosynthesis, and alanine, aspartate, and glutamate metabolism pathways were identified. This is the first study onhighlights the chickpea -A. rabiei interaction at a metabolite level and shows how A. rabiei differentially alters the metabolite profile of resistant and susceptible chickpea accessions and is probably exploiting the chickpea defense pathways in its favor.